Analisis Kesejahteraan Rumah Tangga Petani Padi Sawah Berdasarkan Luas Lahan Garapan di Desa Sale, Kabupaten Rembang - Novindra Novindra; Zumrotul Arifah (Journal of Integrated Agribusiness, 2024)
Rice farming in Sale Village is the population's main occupation to earn income. Less land makes it easier for rice farming in Sale Village to make economic profits, so farmers have to look for additional income both in and outside of agriculture to achieve prosperity that is considered sufficient to meet their household needs. The objectives of this research are (1) to analyze household income and (2) to analyze the level of farmer welfare. The method used in this research is an analysis of income, expenditure, and household welfare using criteria (Sajogyo, 1997) and the BPS poverty line. The research results show that farming is the most significant contribution to household income for small, medium, and large land farmers. The household expenditure value of lowland rice farmers is above the welfare criteria and is classified as a moderate and not poor household.